Art Moscow : The Comedy : The Funny Side of the Moving Image - Degot, Ekaterina (Moscow : Art Moscow Foundation Moscow, 2005)
Alimpiev, Viktor ; Alys, Francis ; Blue Soup ; Chernysheva, Olga ; Fischli & Weiss ; Gutov, Dmitri ; Land, Peter ; Leger, Fernand ; Murphy, Dudley ; Nilin, Vikenty ; Rosefeldt, Julian ; Signer, Roman ; Wurm, Erwin
biog. per kunstenaar
Russisch
Engels
Exhibition. Art Moscow : The Comedy. Central House of Artist Moscow. Art Moscow Foundation Moscow. 24.05.2005 - 29.05.2005
boek
Keywords: Moskou; Rusland